A Case of Loeffler's Endocarditis Associated with Churg-Strauss Syndrome - Seo, Jeong-Sook (Korean Society of Echocardiography, 2010)
Loeffler's endocarditis is generally caused by hypereosinophilic syndrome. It is a restrictive cardiomyopathy characterized with eosinophilia and eosionophilic penetration leading to the fibrous thickening of endocardium of both ventricles, apical obliteration and heart failure. We report a case of a 23-year-old male with Loeffler's endocarditis caused by Churg-Strauss syndrome. The echocardiogram showed that biventricular failure with large thrombus in left ventricle. His symptoms and typical echocardiographic findings markedly improved within 2 months after treatment for Churg-Strauss syndrome.